A Detailed Analysis of Software Cost Estimation Using Cosmic-FFP - Kumar, Gaurav; Bhatia, Pradeep Kumar (Review of Computer Engineering Research, 2015)
Software cost estimation is one of the most challenging tasks in software engineering. For the estimation, Function points are useful in the business application software domain and problematic in the real-time software domain. Full Function Points (FFP) are useful for functionality-based estimation, specifically for real-time and embedded software. Functional size measurement method that has user view of functional requirements developed by Common Software Measurement International Consortium (COSMIC) called COSMIC-FFP. By using COSMIC-FFP model, an early prediction of the functional complexity of the software throughout the software development life cycle within given budget constraints, reliability can be done. In this paper, a detailed analysis with process flow of COSMIC-FFP model has been discussed.